Childbirth sitting. - Martínez Chávez, Marco A. (2015)
The present it is prospective study between July  August ot 1993"in 35 women who they had childbirth in position of litotomy and 35 women whose childbirth’s were carried out in position sifting, for which a seat of childbirth’s was compounded (1 720) for like end. The group control (childbirth in decubitussupinelitotomy). Consisted in gestants to term, all the parities, ginecoide pelvis, partogram with curve of alert, eutocic childbirths, pattern of blood of the umbilical cord, score of Apgar, molding of the fetal head. The group of study (childbirth sifting) apart from the parameters already signal the duration of the expulsive was quantified, grade of paim of the contractions, quality of it dynamic uterine, opinion of it patient, of the obstetra, filming of 5 childbirth. It is found that the duration of the expulsive in the group control was of 21,43 minutes and in the group seated of 9,17 minutes, perineal lacerations 14,28% in the group control  and 5,71% in the group of study, the most intense uterine contractions, effective and less painful, the antropometrics values of both groups was similar (size, weigth, craneal perimeter), score of Apgar, grade of riding, moldeaming of the fetal head; is found neonatal policitemy in ~n% of the first 20 childbirth’s which decreased to 6,66% in the last 15 childbirth’s when the technique of attention was changed of the newly born (place it above the mother and wait I to 2 minutes before cutting the cord).